"Często zmieniane nicki gwarancją higieny forumowej" - problem percepcji tożsamości użytkownika forum internetowego w kontekście operowania nickami = "Often changed nicknames as a guarantee of online forum hygiene" - the problem of the user`s identity perception in the context of using nicknames - Więckiewicz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper concerns the issue of the online forum sers` identity in the context of changing nicknames. Forum users mostly don`t meet "outside the net" and identity of other users receive only through the prism of posts signed with a nickname, so the nickname identifies the forum user in a very distinct way (it`s like a trademark).
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie